Sound Generator: Analysis of the Effectiveness of Noise in the Habituation of Tinnitus - Mondelli, Maria Fernanda Capoani Garcia; Cabreira, Aline Faure; Matos, Izabella Lima de; Ferreira, Maria Carolina; Rocha, Andressa Vital (International Archives of Otorhinolaryngology, 2020)
Introduction Tinnitus is a disorder that affects 10 to 15% of de world's population. Sound therapy performed through hearing aids (HAs) with integrated sound generator (SG) is one of the forms of tinnitus treatment.Objective To analyze the effectiveness of four masking noises in relieving tinnitus in individuals with mild and moderate bilateral sensorineural hearing loss and their influence in speech perception.Methods The participants were 35 individuals with tinnitus and mild and moderate bilateral sensorineural hearing loss, divided into four groups. All groups underwent HA and SG adaptation, being regulated in the combined mode (HA and SG). In group 1 (G1), the white noise stimulus was applied, in group 2 (G2), pink noise was applied, in group 3 (G3), speech noise, and in group 4 (G4), the high tone was applied. All patients were subjected to the following procedures: audiological diagnosis, acuphenometry, tinnitus handicap inventory (THI), visual analogue scale (VAS), and hearing in noise test (HINT). The procedures were performed prior to and after hearing intervention, and after 3 months of use of HA and SG.Results All groups presented a statistically significant difference for the THI, VAS, and HINT pre and postintervention. In the case of the HINT, only pink noise presented a significant difference. However, in the comparation among groups there was no significant difference.Conclusion The present study made it possible to conclude that the four noises were equally effective in relieving tinnitus, with no statistically significant differences between the analyzed groups.
Keywords: tinnitus; hearing loss; hearing aids